2013
DOI: 10.1002/etc.2128
|View full text |Cite
|
Sign up to set email alerts
|

The role of silver and vanadium release in the toxicity of silver vanadate nanowires toward Daphnia similis

Abstract: Abstract-Nanomaterials are used in a wide spectrum of applications, including nanowires that are objects with at least one of its dimensions in the range of 1 to 100 nm. Recently, a new type of silver vanadate nanowire decorated with silver nanoparticles (SVSN-LQES1) with promising antimicrobial activity against different pathogenic bacteria was described. The objective of the present study was to evaluate the role of silver and vanadium release in the acute toxicity of this material using Daphnia similis. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
6
26
0
4
Order By: Relevance
“…Artal et al (2013) also reported small bubbles under the carapace of D. similis exposed the silver nanowires that were similar to those observed in this work. The organisms exposed to CuSO 4 suffered great damage with exposure of internal organs (Figure 3c).…”
Section: Mv)supporting
confidence: 79%
See 1 more Smart Citation
“…Artal et al (2013) also reported small bubbles under the carapace of D. similis exposed the silver nanowires that were similar to those observed in this work. The organisms exposed to CuSO 4 suffered great damage with exposure of internal organs (Figure 3c).…”
Section: Mv)supporting
confidence: 79%
“…Lin et al (2012) (Knie & Lopes, 2004;Paschoalino et al, 2010). Furthermore, daphnids are considered a keystone species in aquatic toxicology because they are filter-feeders and are able to ingest NPs (Artal et al, 2013).Tests employing Daphnia have been used to evaluate the nanomaterials ecotoxicity, due to be important links in the food chain from algae consumed by them, and the fish that are predators (Paschoalino et al, 2010).They have also been proposed as a model organism for the ecotoxicological testing of nanomaterials (Paschoalino et al, 2010;Artal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These droplets were already observed when daphnids were exposed to various toxic substances such as insecticide or nanoparticles [61][62][63]. Generally, the accumulated lipid droplets indicate abnormal synthesis or metabolism of lipids and it is plausible that samples corresponding to t 0 and t f reaction times could alter lipid homeostasis in D. magna.…”
Section: Ecotoxicity and Genotoxicity Of Treated Watermentioning
confidence: 99%
“…However, for clinical application, the biocompatibility of these modified materials needs to be evaluated. Artal et al (30) has demonstrated that silver vanadate nanowires decorated with silver nanoparticles can be toxic to Daphinia similis as a function of silver (Ag) release. …”
mentioning
confidence: 99%